PERUBAHAN KANDUNGAN KAROTEN DAN AKTIVITAS ANTIOKSIDAN PADA WORTEL (Daucus carota) SELAMA PROSES PEREBUSAN - Yudiar, Haniel; Lindayani, Linda; Nugrahedi, Probo Y. (VITASPHERE, 2012)
Health is one of the main factors contributing to the quality of life. Good health is resulted from various factors. including the quality and quantity of food intake. Many researches show that nutritional factors contribute in the prevention of degenerative diseases, such as heart disease and cancer. Carrot is one kind of root vegetables that widely consumed, contains health promoting compounds. particularly carotenoids. Boiling is one of ca"ot processing methods usually done at household level. The boiling of ca"ot was supposed to influence carotene content of carrot and therefore would change its antioxidant activity. The aim of this study was to study the changes of carotene content and antioxidant activity of carrot during boiling process. The carotene content and antioxidant activity were analyzed by open-column chromatography (OCC) followed by spectrophotometer and by 2,2-diphenylI- picrylhydrazy/ (DPPH) methods, respectively. This study found that carrot boiledfor 24-30 minutes had the highest antioxidant activity. and more than 30 minutes of boiling. the antioxidant activity was decreased. In order to get the highest carotene content and antioxidant activity of boiled ca"ot {with usual shape made in household processing. which is cross-sectional slices with 2-4 mm thickness}. the boiling time therefore should be 24-30 minutes.